POLYMERIC SILVER NANOCARRIERS: INNOVATIVE DRUG DELIVERY STRATEGIES FOR ALZHEIMER’S DISEASE AND NEURODEGENERATIVE DISORDERS - KINKAR, HIMANSHU; DHARPURE, DIVYANSH; TUMME, DHANASHRI (International Journal of Current Pharmaceutical Research, 2026)
Alzheimer’s disease (AD) is a multifactorial neurodegenerative disorder marked by amyloid-β plaque accumulation, tau hyperphosphorylation, oxidative stress, neuroinflammation, and progressive cognitive impairment. The clinical effectiveness of conventional therapies is limited due to poor brain bioavailability, rapid systemic clearance, and the restrictive nature of the blood–brain barrier (BBB), resulting mainly in symptomatic relief rather than disease modification. In this context, polymeric silver nanocarriers (PSNs) have emerged as a promising nanotherapeutic approach for targeted and controlled drug delivery to the central nervous system. By integrating the antioxidant and anti-inflammatory properties of silver nanoparticles with the biocompatibility, stability, and controlled release characteristics of polymeric matrices such as PLGA, PEG, and chitosan, PSNs enable enhanced drug encapsulation, sustained release, and efficient BBB penetration through surface functionalization and receptor-mediated transport mechanisms. Preclinical in vitro and in vivo studies demonstrate that PSNs can effectively reduce amyloid-β aggregation, inhibit tau pathology, attenuate oxidative stress, and suppress neuroinflammatory responses, leading to improved neuronal survival and cognitive outcomes. Alternative delivery strategies, including intranasal and nose-to-brain routes, further improve therapeutic efficiency while minimizing systemic toxicity. Although challenges related to long-term safety, neurotoxicity, scalability, and regulatory approval remain, polymeric silver nanocarriers represent a versatile and multifunctional platform with significant potential for advancing disease-modifying therapies in Alzheimer’s disease.